Traveling-wave-based Fault Location using Time Delays between Modal Components in Electrical Distribution Systems - Lei, Yang; Yang, Fan; Yin, Zhijiang; Tang, Jinrui; Zhang, Guoqing; Ma, Bo; Shen, Yu; Yang, Zhichun (Recent Advances in Electrical & Electronic Engineering, 2024)
Background: The distribution feeders usually include many laterals, too many sensors need to be installed to locate the fault positions in electrical distribution systems by using the traditional double-ended traveling-wave-based fault-location methods. Objective: Fault location based on the time delays between the moments of the first wavefronts of zero-mode voltages and that of aerial-mode voltages arriving at one end of the distribution feeder. Methods: Large decomposition level in wavelet transformation is adopted in this paper to obtain the zero-mode velocity. Results: Both theoretical research and simulation experiments have proved that the proposed fault location method can greatly improve the accuracy of the fault location in the electrical distribution systems without many sensors. Conclusion: The proposed fault location method can provide one feasible way to locate the faults in the electrical distribution systems.
Keywords: Electrical distribution systems